(untitled) (New York, 2010)
Presents a complete review for the emergency medicine written boards from pre-eminent NYC emergency departments, including intensive review of emergency medicine essentials, Q&A, and an electronic visual stimulation review with color images and accompanying cases.
Keywords: Emergency medicine,Thuốc cấp cứu